Pengaruh Model Cased Based Learning Berbantuan Flipped Clasroom terhadap Keterampilan Berpikir Kritis Siswa Ditinjau dari Gaya Kognitif - Arsana, Juli; Sriartha, I Putu; Sukadi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The research aims to analyze the influence of learning models on students' critical thinking skills in terms of cognitive style with quasi-experimental research on learning. The research design used is a factorial design, using two learning models, namely the Cased Based Learning Model Assisted by Flipped Classrooms in the experimental group and the conventional learning model in the control group. Samples were taken randomly using lottery and cognitive style tests to determine field independent cognitive style and field dependent cognitive style. The total sample used was 80 class XI students. Data on critical thinking skills was taken using a critical thinking skills test which has a high reliability value. The data analysis technique used is ANOVA AB. Based on the results of data analysis, it was found that: 1) There are differences in critical thinking skills between groups of students who study with the CBL model assisted by Flipped Classroom and groups of students who study with conventional learning. 2) There are differences in the critical thinking skills of the group of students who have the Field Independent (FI) cognitive style and the group of students who have the Field Dependent (FD) cognitive style. 3) There is an interaction between learning models and cognitive styles on critical thinking skills.